Reliable multi-path communication for IoT based solar automated monitoring as motivation towards multi-farming hydroponic - Wong, Adam Yoon Khang; Jamil Alsayaydeh, Jamil Abedalrahim; Mohamat Gani, Johar Akbar; Pusppanathan, Jaysuman; Awang Teh, Azman; Ismail, Albert Feisal @ Muhd Feisal; Tan, Kim Geok (International Association of Online Engineering, 2023)
The current reliance on single-path communication presents limitations for effectively monitoring and controlling critical parameters that are essential for hydroponic success. This hampers the achievement of optimal plant growth and overall system performance in multi-farming hydroponic setups. The issue lies in the inherent vulnerabilities of single-path communication, which can result in data loss and transmission errors. Therefore, reliable multi-path communication is essential for Internet of Things (IoT)-based automated monitoring systems. The research aims to enhance monitoring and control capabilities in multi-farming hydroponic environments by integrating advanced communication technologies. Utilizing the ESP microcontroller in conjunction with the Painless Mesh library enables seamless communication among nodes, facilitating real-time data exchange and control. Additionally, app-based dashboard monitoring offers a user-friendly interface for remote monitoring. The findings demonstrate that reliable multi-path communication, combined with app-based dashboard monitoring, promotes optimal plant growth, efficient resource allocation, and sustainable multi-farming practices. In summary, this research contributes to a deliberate efficiency increase of 30% in pH level, 25% in humidity level, and 35% in temperature level. This paves the way for adopting efficient multi-farming hydroponic solutions that are based on resource-efficient energy usage.